The Level of Community Preparedness in Facing Drought Disasters - Brian Pradana; Ade Pugara; Bagus Nuari Priambudi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
In 2024, a drought in Kajen District caused many agricultural lands to fail and hampered community activities. Kajen District is the capital city that supports the center of activities. If a drought occurs, of course, this will inhibit the activities in it. This study aims to analyze the level of drought disaster preparedness in Kajen District. Specifically, the research location is a village affected by drought, namely in Gejlig, Kebonagung, Sambiroto, Tambakroto, and Tanjungsari Villages. This study uses a quantitative deductive approach, a questionnaire in the affected villages totaling 104 questionnaires. Based on the drought disaster preparedness analysis results, it is known that the parameter with the highest value is knowledgeability and attitude towards the risk of disaster, which is 98.08%. For cluster analysis, it was found that Gejlig, Sambiroto, and Tambakroto Villages were in class 1 (high), Kebonagung Village (medium), and Tanjungsari Village were in class 3 (low). When viewed based on the Pekalongan Regency RTRW 2020 - 2040, Kajen District is directed as ”PKL”, namely an urban area that functions to serve district-scale activities or several districts so that it needs to be supported by a clean water supply so that drought does not occur. With this drought disaster, the Regency Government must encourage policies and protocols to overcome drought disasters, such as irrigation infrastucture rehabilitation, land and water conservation and reforestation, especially in the Southern Part of Pekalongan Regency.